2020
DOI: 10.1007/s00264-020-04623-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of outcomes after revision surgery using porous titanium custom-made implants for severe acetabular septic bone defects

Abstract: Purpose Acetabular bone loss is a challenging problem in revision total hip arthroplasty (rTHA). Severe bone loss is not uncommon especially in periprosthetic joint infection. Surgical options, including revision shells, rings, and cages-with or without bone allograft-are affected by high complication rates and unsatisfactory clinical results. We report our mid-term results of non-flanged, custom-made acetabular components in staged rTHA. Methods We retrospectively reviewed all patients undergoing two-stage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…However, they did not investigate the position compared to the contralateral side. Others reported satisfying final position of the implants, inclination of the shell or osseointegration, but did not investigate offsets and COR [ 28 , 29 ]. A recently published study by Walter et al showed significant lateralisation and cranialization when CTAC was used [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not investigate the position compared to the contralateral side. Others reported satisfying final position of the implants, inclination of the shell or osseointegration, but did not investigate offsets and COR [ 28 , 29 ]. A recently published study by Walter et al showed significant lateralisation and cranialization when CTAC was used [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been a steady increase in the use of porous titanium customized acetabular implants in revision THA. These implants provide an individualized fit for each patient and achieve satisfactory results, including improvement in hip joint function and good stability even with severe acetabular bone loss or pelvic discontinuity [16][17][18]. However, customized implants are not indispensable if bone loss is not severe.…”
Section: Discussionmentioning
confidence: 99%
“…As only patients treated due to malignant tumors were included in this study, this studies’ results are limited and need to be considered exclusively in this patient collective. This is especially important with a recent emerge of studies describing the use of custom-made pelvic implants and components in revision arthroplasty settings, as this patient collective comes with different demographics and functional status [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%